A theoretical model for organizing and understanding teacher learning opportunities to teach mathematics - Ribeiro, Alessandro Jacques (2020)
Understanding how teacher learning is constituted is an important research area in teacher education with many open questions to be investigated yet. Thereby, in this paper, we present a theoretical model whose main purpose is to enable the design of teacher education programs as well as to guide the understanding of professional learning opportunities for teachers. Based on our research outcomes on teaching and learning algebra and on a literature review, we describe how the model was elaborated and bring some illustrative situations to indicate the model “in action” throughout the teacher education process. The architecture of the program enabled teachers to experience professional learning opportunities linked to mathematical and didactical knowledge regarding patterns and regularities, as well as the opportunity to learn from and with each other, overcoming the isolation caused by daily work in their schools and leading them to explore practices close to their own school reality.